Description Of Social Media Addiction Level And Mental Health Among Adolescents - Ni Kadek Dariyanti; Ni Komang Sukra Andini; Hendro Wahyudi (Yayasan Lentera Mitra Lestari, 2026)
Background: Social media addiction is a problem commonly experienced by adolescents along with the increasing use of digital technology. Excessive use of social media can affect adolescents’ mental health, particularly in maintaining emotional balance and social behavior. Objective: This study aims to determine the level of social media addiction and the mental health condition of adolescents at Public Senior High School 1 North Kuta. Methods: This study employed a descriptive quantitative design with a stratified random sampling technique. A total of 258 students participated as respondents. The research instruments used were a social media addiction questionnaire and the Strengths and Difficulties Questionnaire (SDQ). Results: The results showed that the majority of respondents were aged 15–16 years and were predominantly female. Most respondents had mild (75.6%) and moderate (23.6%) levels of social media addiction. Regarding mental health aspects, 49.6% of respondents were in the normal category, while the borderline and abnormal categories each accounted for 25.2%. Conclusion: Excessive use of social media can have an impact on adolescents’ emotional balance. Wise use of social media and school support through positive activities such as soccer, volleyball, badminton, basketball, running, and dance are expected to help students channel their emotions in a healthy manner and enhance self-confidence.